Distribuição local de energia em corrente contínua: estudo,desenvolvimento e implementação de um Protótipo deNanorrede c.c. dedicado aos setores residencial e comercial - Thiago Ribeiro de Oliveira (2016)
In a scenario dominated by an increasing electricity demand, energy resources deple- tion and by the need for enhancing the energy conservation of the electrical grid and penetration of renewable resources into the energy matrix, the modernization of the elec- trical system infrastructure toward a more optimized, reliable and renewable standard, i.e., toward a Smart Grid with distributed microgrids, is shown to be an ongoing trend. In this context, a promising line of work, dedicated to the development of microgrids associated with commercial and residential buildings, also termed as nanogrids, seeks to enable the deployment of dc power distribution in buildings as a mean to promote higher energy efficiency, better integration with distributed renewable energy resources and storage devices. This thesis addresses the design and development of a dc nanogrid prototype for commercial and residential buildings applications. Design, dimensioning and protection criteria for this new electrical installation will be presented in this work, as well as a description of the nanogrid power management architecture, power converter topologies, control diagrams and stability analysis. A novel method for energy storage system mana- gement in dc nanogrids is also introduced, which provides simultaneously state-of-charge balancing among distributed energy storage units and monitoring of each battery bank charge/discharge process. The nanogrid behavior is investigated both through simulations and experimental results obtained in a 2kW prototype implemented the laboratory.